An Adaptation of the RAND/UCLA Modified Delphi Panel Method in the Time of COVID-19 - Broder MS; Gibbs SN; Yermilov I (Dove Medical Press, 2022)
Michael S Broder, Sarah N Gibbs, Irina Yermilov Outcomes Research, Partnership for Health Analytic Research (PHAR), LLC, Beverly Hills, CA, USACorrespondence: Michael S Broder, Partnership for Health Analytic Research (PHAR), LLC, 280 S Beverly Drive, Suite 404, Beverly Hills, CA, 90212, USA, Tel +1-310-858-9555, Fax +1-310-858-9550, Email mbroder@pharllc.comAbstract: The RAND/UCLA modified Delphi panel method is a formal group consensus process that systematically and quantitatively combines expert opinion and evidence by asking panelists to rate, discuss, then re-rate items. The method has been used to develop medical society guidelines, other clinical practice guidelines, disease classification systems, research agendas, and quality improvement interventions. Traditionally, a group of experts meet in person to discuss results of a first-round survey. After the meeting, experts complete a second-round survey used to develop areas of consensus. During the COVID-19 pandemic, this aspect of the method was not possible. As such, we have adapted the method to conduct virtual RAND/UCLA modified Delphi panels. In this study, we present a targeted literature review to describe and summarize the existing evidence on the RAND/UCLA modified Delphi panel method and outline our adaptation for conducting these panels virtually. Transitioning from in-person to virtual meetings was not without challenges, but there have also been unexpected advantages. The method we describe here can be a cost-effective and efficient alternative for researchers and clinicians.Keywords: Delphi panel, expert panel, consensus, virtual meeting, COVID-19, pandemic